Bioprinted Three-Dimensional Cell-Laden Hydrogels to Evaluate Adipocyte-Breast Cancer Cell Interactions - Sarah Chaji; Jenna Al-Saleh; Cheryl T. Gomillion (Gels, 2020)
Three-dimensional (3D) bioprinting, although still in its infancy as a fabrication tool, has the potential to effectively mimic many biological environments. Cell-laden 3D printed structures have demonstrated to be an improvement from the widely used monolayer platforms, largely because of recapitulation of native tissue architecture with the 3D structures. Thus, 3D in vitro models have been increasingly investigated for improved modeling of cell and disease systems, such as for breast cancer. In the present work, multicellular cell-laden hydrogels comprised of adipocytes and breast cancer cells were bioprinted and evaluated. An ideal bioink of 3:2 5% alginate was determined to mimic the tissue stiffness observed in a physiological breast cancer tumor environment. Rheological characterization and degradation studies were performed to verify the stability of the artificial breast hydrogel environment. It was found that both the breast cancer cells and adipocytes remained viable directly after printing and throughout the 10-day culture period within the printed hydrogels. Direct printing of the cells in co-culture resulted in morphology changes and variations in cell localization within printed structures. Overall, the feasibility of efficiently fabricating multicellular cell-laden bioprinted models of the breast tumor microenvironment was established.